Effects of progressive resistance training combined with a protein-enriched lean red meat diet on health-related quality of life in elderly women: secondary analysis of a 4-month cluster randomised controlled trial. Issue 11 (19th July 2017) - Torres, Susan J.; Robinson, Sian; Orellana, Liliana; O'Connell, Stella L.; Grimes, Carley A.; Mundell, Niamh L.; Dunstan, David W.; Nowson, Caryl A.; Daly, Robin M.
Abstract: Resistance training (RT) and increased dietary protein are recommended to attenuate age-related muscle loss in the elderly. This study examined the effect of a lean red meat protein-enriched diet combined with progressive resistance training (RT+Meat) on health-related quality of life (HR-QoL) in elderly women. In this 4-month cluster randomised controlled trial, 100 women aged 60–90 years (mean 73 years) from self-care retirement villages participated in RT twice a week and were allocated either 160 g/d (cooked) lean red meat consumed across 2 meals/d, 6 d/week or ≥1 serving/d (25–30 g) carbohydrates (control group, CRT). HR-QoL (SF-36 Health Survey questionnaire), lower limb maximum muscle strength and lean tissue mass (LTM) (dual-energy X-ray absorptiometry) were assessed at baseline and 4 months. In all, ninety-one women (91 %) completed the study (RT+Meat ( n 48); CRT ( n 43)). Mean protein intake was greater in RT+Meat than CRT throughout the study (1·3 (sd 0·3) v . 1·1 (sd 0·3) g/kg per d, P <0·05). Exercise compliance (74 %) was not different between groups. After 4 months there was a significant net benefit in the RT+Meat compared with CRT group for overall HR-QoL and the physical component summary (PCS) score ( P <0·01), but there were no changes in either group in the mental component summary (MCS) score. Changes in lower limb muscle strength, but not LTM, were positively associated with changes in overall HR-QoL (muscle strength, β : 2·2 (95 % CI 0·1, 4·3), P <0·05). In conclusion, a combination of RT and increased dietary protein led to greater net benefits in overall HR-QoL in elderly women compared with RT alone, which was because of greater improvements in PCS rather than MCS.